Comunicação em rede e alternativas democráticas: um estudo sobre junho de 2013 e novas formas de atuação política - Ferreira, Marco Aurélio (2018)
The ideas generated in any locality soon accede the virtual space. They spread and are concretized in different places, be it a business room, a factory floor, a schoolyard, a family house or even in streets and public spaces. At the turn of the century, several large-scale protest demonstrations took the streets of urban centers around the world and an unprecedented element could be perceived among its agents: the intensive association of protesters with communication networks, which have as main characteristic the abundance and high-speed circulation of information. However,in the midst of so many transformations and novelties, digital information and communication technologies remain, to some extent, surrounded by unknowns about their potentialities, properties and functions in the context of contemporary democracy, as well as the cultural consequences of their application, reason which expresses the urgency to reflect on its nature and form of participation in collective dynamics, political mobilizations and social movements. This research analyzes the role played by digital communication networks in protests occurred in the city of São Paulo in June 2013, in order to delineate, analyze and understand some of the characteristics of its successful way to disseminate information and its power to persuade and engage citizens that were not previously linked to cultural-political groups or social movements. In sum, it is proposed to investigate how and why the ICTs used in digital communication networks have assumed a preponderant role in June’s disputes and to raise interpretations about their nature and the issues ofcommunicationin contemporary society. The methodology of the work assumes hybrid formulation between bibliographic research, documentary analysis and, consequently, conceptual articulation, from which the analyzes were carried out